ISLAMIC GROUP PLAY THERAPY: UPAYA PENGEMBANGAN KETERAMPILAN HELP SEEKING BEHAVIOUR DALAM MENGHADAPI KEKERASAN SEKSUAL PADA ANAK - Ikhwanisifa Ikhwanisifa; Raudatussalamah Raudatussalamah; Reni Susanti (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
Sexual violence against children is increasingly prevalent, in some cases, it is found that the child's lack of skills in dealing with situations that threaten him. The purpose of this study is to look at the effectiveness of Islamic Group Play Therapy in improving help-seeking behavior skills in children who are vulnerable to sexual harassment or violence. Respondents in this study were 15 children who have experienced sexual violence and children who are vulnerable to sexual harassment or violence in Siak Regency. The data analysis technique is a paired sample test technique. The results of the overall analysis showed that there was no increase in skills to seek help in child victims of sexual violence with a value of t-1.976 with a significance level of 0.068. However, an increase in skills occurred in the informal dimension, namely an increase in the behavior of asking for help from others with a value of -3.761 at a significance level of 0.002, meaning that the subject was able to ask for help from others during sexual violence. There is an increase in helping yourself with a t value of 4795 at a significance level of 0.000, meaning that there has been an attempt by the subject to help himself so that the subject is not just silent when he experiences sexual violence.